Marckalada: The First Mention of America in the Mediterranean Area (c. 1340) - Chiesa P. (Terrae Incognitae, 2021)
The Cronica universalis written by the Milanese friar Galvaneus Flamma (it. Galvano Fiamma, d. c. 1345) contains an astonishing reference to a "terra que dicitur Marckalada", situated west from Greenland. This land is recognizable as the Markland mentioned by some Icelandic sources and identified by scholars as some part of the Atlantic coast of North America. Galvaneus’s reference, probably derived by oral sources heard in Genoa, is the first mention of the American continent in the Mediterranean region, and gives evidence of the circulation (out of the Nordic area and 150 years before Columbus) of narratives about lands beyond Greenland. This article provides a transcription of the passage, explains its context in the Cronica universalis, compares it to the other (Nordic) references of Markland, and discusses the possible origin of Galvaneus’s mention of Markland in light of his biography and working method.